Perbandingan Faktor Penunjang Dan Penghambat Pembelajaran Renang Pada Siswa SMP Reguler Dan Kelas Khusus Olahraga Grobogan - Pastika Candra Nurjanah; Adi S; Supriyono; Bhayu Billiandri (Universitas Negeri Semarang, 2024)
The background of this study is that there is no research that comprehensively discusses the supporting and inhibiting factors of swimming learning in one study and there has been no related research conducted at SMP special sports classes. The purpose of this study is to determine the comparison of inhibiting factors for swimming learning in regular junior high schools and special sports classes. This research uses a quantitative method with a descriptive approach model. The data collection method is a questionnaire. Data analysis in this study used SPSS version 29. The results showed that (1) The supporting factors for swimming learning in regular junior high schools were in the moderate category with a percentage of 40.0%, while in special sports class junior high schools were in the moderate category with a percentage of 33.3%. (2) The inhibiting factors for swimming learning in regular junior high schools are in the moderate category with a percentage of 40.0%, while in special sports class junior high schools are in the moderate category with a percentage of 33.3%. (3) Based on the results of research in regular junior high schools and sports special class junior high schools on the supporting and inhibiting factors of swimming learning, there are significant differences